2020
DOI: 10.1109/tifs.2020.2968183
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis Attacks on Logic Locking

Abstract: This paper proposes Functional Analysis attacks on Logic Locking algorithms (abbreviated as FALL attacks). FALL attacks have two stages. Their first stage is dependent on the locking algorithm and involves analyzing structural and functional properties of locked circuits to identify a list of potential locking keys. The second stage is algorithm agnostic and introduces a powerful addition to SAT-based attacks called key confirmation. Key confirmation can identify the correct key from a list of alternatives and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Both SFLL-HD and SFLL-flex c×k utilize AND-trees which leave structural hints for an opportune attacker. Such an attack has been demonstrated recently by Sirone et al [33]; the authors deciphered the key successfully (even without oracle access). At the time of writing, no attacks have been demonstrated on SFLL-fault yet.…”
Section: Advanced Logic Locking Schemesmentioning
confidence: 87%
“…Both SFLL-HD and SFLL-flex c×k utilize AND-trees which leave structural hints for an opportune attacker. Such an attack has been demonstrated recently by Sirone et al [33]; the authors deciphered the key successfully (even without oracle access). At the time of writing, no attacks have been demonstrated on SFLL-fault yet.…”
Section: Advanced Logic Locking Schemesmentioning
confidence: 87%
“…Further research revealed that these obfuscation techniques are vulnerable to removal [11], Bypass [24] and FALL [25] attacks. In a removal attack, these SAT hard blocks are identified using Signal Probability Skew (SPS) attack [11] and removed.…”
Section: A Acyclic Logic Obfuscationmentioning
confidence: 99%
“…SFLL was briefly considered the state-of-the-art SAT resistant logic obfuscation technique. Then a recent functional analysis attack (FALL) [58] was proposed that uses structural and functional analyses on the locked design to identify the locking key, without even having access to an oracle. EPIC attack [55] uses a hill-climbing search based algorithm that monitors test response to guess the secret key.…”
Section: Vulnerabilities Of the Dftmentioning
confidence: 99%